The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1111/j.1439-0531.2008.01246.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Oestrous Induction Response, Oestrous Duration, Fecundity and Fertility in Awassi Ewes During the Non‐breeding Season Utilizing both CIDR and Intravaginal Sponge Treatments

Abstract: The aim of this study was to investigate characterization of oestrous response, onset of induced oestrus, oestrous duration, fecundity and fertility in Awassi ewes treatment with intravaginal sponges and Controlled Intravaginal Drug Release (CIDR) devices in combination with pregnant mare serum gonadotropin (PMSG) under local environmental conditions during the non-breeding season. A total of 62 ewes were divided into three groups. Group CIDR (n = 20) was treated with CIDR devices for 12 days and 400 IU PMSG w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
14
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 29 publications
(56 reference statements)
6
14
3
Order By: Relevance
“…For example, Arroyo-Ledezma et al (2013) used CIDR or PGF2 Alpha protocols in hair sheep did not find differences in estrus presentation, but ET-OE interval was different (P≤0.05). Previous studies (Ozyurtlu, et al 2010) have reported shorter estrus duration using progestogens in estrus synchronization than those reported in this trial. In ewes treated with Cloprostenol, duration of estrus was more homogenous according to the variation coefficient (15.19 and 4.46 % for progestogen and Cloprostenol).…”
Section: Discussioncontrasting
confidence: 69%
“…For example, Arroyo-Ledezma et al (2013) used CIDR or PGF2 Alpha protocols in hair sheep did not find differences in estrus presentation, but ET-OE interval was different (P≤0.05). Previous studies (Ozyurtlu, et al 2010) have reported shorter estrus duration using progestogens in estrus synchronization than those reported in this trial. In ewes treated with Cloprostenol, duration of estrus was more homogenous according to the variation coefficient (15.19 and 4.46 % for progestogen and Cloprostenol).…”
Section: Discussioncontrasting
confidence: 69%
“…The average body weight of adult Awassi ewe is 45-55 kg while the ram weighs 60-90 kg (Degen and Benjamin 2003;Ozyurtlu et al 2010). The body is covered with long coarse wool of creamy white color except for the face.…”
Section: Breed Descriptionmentioning
confidence: 99%
“…Factors that can affect the reproductive activity in sheep include season, photoperiod, breed, age, nutrition, diseases, stress, management, environment, and male factors (Amer and Hazzaa 2009;Ozyurtlu et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally the system can be effectively used even in non cycling animals. However successful protocols must not only provide tight synchrony of estrus but also have acceptable fertility rates (Godfrey et al 1997;khan et al 2006;Ozyurtlu et al 2008). Synthetic progestins for estrus induction and synchronization are commercially available either as ear implants or intravaginal devices.…”
Section: Discussionmentioning
confidence: 99%